Penerapan Metode Earned Value Analysis Terhadap Waktu Penjadwalan: Studi Kasus: Pembangunan Gedung Ruang Kelas Baru (RKB) Pada Madrasah Aliyah Negeri (MAN) Kab. Karawang - Syapril Janizar (Institut Teknologi Garut, 2023)
Project management is an activity which consists of planning, leading, organizing, and controlling the company's organizational resources to achieve predetermined organizational goals within a certain period of time with certain resources. Case study on the Project for the Construction of a New Classroom Building (RKB) for the State Madrasah Aliyah (MAN) Kab. Karawang which is located Karawang, West Java 41314. Analyzing the project using the concept of Earned Value Analysis which is focused on the implementation of the Project for the Construction of a New Classroom Building (RKB) of the State Madrasah Aliyah (MAN) Kab. Karawang. Knowing and adding insight about cost and time control on a project by applying Earned Value Analysis. The work completion time is in accordance with the work plan so that the work can be completed according to schedule.